Ultrathin Ga2O3 Glass: A Large‐Scale Passivation and Protection Material for Monolayer WS2. Issue 3 (4th December 2020) - Wurdack, Matthias; Yun, Tinghe; Estrecho, Eliezer; Syed, Nitu; Bhattacharyya, Semonti; Pieczarka, Maciej; Zavabeti, Ali; Chen, Shao‐Yu; Haas, Benedikt; Müller, Johannes; Lockrey, Mark N.; Bao, Qiaoliang; et al.
Abstract: Atomically thin transition metal dichalcogenide crystals (TMDCs) have extraordinary optical properties that make them attractive for future optoelectronic applications. Integration of TMDCs into practical all‐dielectric heterostructures hinges on the ability to passivate and protect them against necessary fabrication steps on large scales. Despite its limited scalability, encapsulation of TMDCs in hexagonal boron nitride (hBN) currently has no viable alternative for achieving high performance of the final device. Here, it is shown that the novel, ultrathin Ga2 O3 glass is an ideal centimeter‐scale coating material that enhances optical performance of the monolayers and protects them against further material deposition. In particular, Ga2 O3 capping of monolayer WS2 outperforms commercial‐grade hBN in both scalability and optical performance at room temperature. These properties make Ga2 O3 highly suitable for large‐scale passivation and protection of monolayer TMDCs in functional heterostructures. Abstract : 2D transition metal dichalcogenides have promising properties for future semiconductor technologies. Their integration into functional devices requires cost‐efficient and large‐scale passivation and protection against material deposition. This work introduces ultrathin Ga2 O3 glass as a new, scalable capping material for monolayer WS2 . It exhibits a novel passivation mechanism and offers extraordinary protection against deposition of dielectric materials, for example, for top‐gating.